2021
DOI: 10.3174/ajnr.a6969
|View full text |Cite
|
Sign up to set email alerts
|

CT Perfusion: More Than What You Thought

Abstract: A cute stroke treatment has dramatically changed in the past decade. Boundaries are crossed, and previous axioms are no longer relevant. The results of the DWI or CTP Assessment with Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention with Trevo (DAWN) and Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3 (DEFUSE-3) trials, 1,2 examining endovascular thrombectomy (EVT) in the late timeframe (6-24 hours from stroke onset), have thrust perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It must be noted that the above-mentioned studies reported GIC had important limitations, as they used only NECT follow-up for the evaluation of FIV. That approach was likely error-prone as MRI has been shown to be the most accurate diagnostic method for assessing acute ischemic changes [ 26 , 27 , 28 , 29 ]. Due to consistent MRI follow-up, we consider our volumetric FIV data to be more reliable; moreover, all subjects underwent MRI within the same time interval, scans were performed on the same 1.5T MRI scanner and the FIV was measured by one neuroradiologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that the above-mentioned studies reported GIC had important limitations, as they used only NECT follow-up for the evaluation of FIV. That approach was likely error-prone as MRI has been shown to be the most accurate diagnostic method for assessing acute ischemic changes [ 26 , 27 , 28 , 29 ]. Due to consistent MRI follow-up, we consider our volumetric FIV data to be more reliable; moreover, all subjects underwent MRI within the same time interval, scans were performed on the same 1.5T MRI scanner and the FIV was measured by one neuroradiologist.…”
Section: Discussionmentioning
confidence: 99%
“…For the measurement of FIV, they used a 5–7-day NECT follow-up. It is well known that CT sensitivity for acute ischemic changes is lower than MRI sensitivity [ 26 , 27 , 28 , 29 ]. Moreover, the follow-up was conducted 5–7 days after EVT, which is an important difference from our follow-up, which was conducted one day after EVT.…”
Section: Discussionmentioning
confidence: 99%
“…Available, rapid, and suitable for critically ill patients needing prompt intervention, imaging biomarkers are good for efficacy and safety outcome evaluation, as fast and reliable imaging biomarker interpretations are critical for making influential therapeutic decisions and prognostications in patients with acute ischemic stroke [ 142 , 143 ]. CT perfusion imaging can provide information about tumor vasculature and in vivo assessment of vascular parameters such as permeability surface area-product (PS) and relative CBV.…”
Section: Main Textmentioning
confidence: 99%